Screening questionnaire for documentation of medical history and diagnostic findings in dry eye disease - Jacobi, Christina; Bellios, N.; Jacobi, A.; Kruse, Friedrich; Cursiefen, Claus (Klinische Monatsblätter für Augenheilkunde, 2011)
Keratoconjunctivitis sicca is one of the most common ocular diseases world-wide. These patients suffer from severe symptoms which lead to an extremely reduced quality of life. Dry eye syndrome constitutes a major diagnostic and therapeutic challenge to all ophthalmologists because there is often a discrepancy between objective ocular signs and subjective symptoms of the patients. Furthermore, there exist only few causal therapeutic options. The physician-patient relationship plays an outstanding role in this condition. For the treatment of moderate to severe dry eye syndrome, special dry eye clinics have proved to be extremely useful. For follow-up measurements as well as the realisation of evidence-based medicine and quality control, it is a fundamental necessity to document symptoms, signs and therapy of these patients in order to optimise therapeutic strategies. For this purpose, we have developed special forms and standardised questionnaires for the individual documentation of medical history and diagnostic findings. To objectively assess the patient's complaints we use the "ocular surface disease index" (OSDI score). Only the establishment of standardised diagnostic and therapeutic algorithms with the help of special forms and questionnaires can help in the long run to improve the treatment of these severely affected patients.
EVALuna2:21043